2011
DOI: 10.5732/cjc.010.10074
|View full text |Cite
|
Sign up to set email alerts
|

Advancement and prospects of tumor gene therapy

Abstract: Gene therapy is one of the most attractive fields in tumor therapy. In past decades, significant progress has been achieved. Various approaches, such as viral and non-viral vectors and physical methods, have been developed to make gene delivery safer and more efficient. Several therapeutic strategies have evolved, including gene-based (tumor suppressor genes, suicide genes, antiangiogenic genes, cytokine and oxidative stress-based genes) and RNA-based (antisense oligonucleotides and RNA interference) approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 67 publications
1
16
0
Order By: Relevance
“…The primary measure for the treatment of esophageal carcinoma is surgery; however, recurrence is observed postoperatively in certain patients and affects the survival of these patients (25). The present study confirmed that patients with high expression of activin A preserved a lower cumulative survival rate and a higher cumulative recurrence rate compared with patients with low expression of activin A.…”
Section: Discussionsupporting
confidence: 82%
“…The primary measure for the treatment of esophageal carcinoma is surgery; however, recurrence is observed postoperatively in certain patients and affects the survival of these patients (25). The present study confirmed that patients with high expression of activin A preserved a lower cumulative survival rate and a higher cumulative recurrence rate compared with patients with low expression of activin A.…”
Section: Discussionsupporting
confidence: 82%
“…Recently, a wide variety of other gene therapies have been investigated in many malignancies, such as antiangiogenic, tumor-suppressor, cytokine-based and oxidative-based gene therapy (24). In addition, cell cycles regulate growth and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Biological therapy includes many methods such as target therapy, gene therapy and tumor vaccine, of which gene therapy is the most recent research topic (3). Evidence has shown that the occurrence and development of malignant tumor is closely related to gene alteration (3). Gene therapy may change the biological behavior of the tumor cells by correcting or repairing the malignant genes.…”
Section: Introductionmentioning
confidence: 99%
“…The members of this family play an important role in the occurrence and development of many tumors, therefore cytokine therapy is commonly used for tumor immunotherapy (3,4). In previous studies the focus was on the tumor itself, whereas increasingly investigations have focused on the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%